PENGARUH PENGGUNAAN ASAM ORGANIK UNTUK MENURUNKAN KADAR LOGAM TIMBAL (Pb) PADA DAGING SIPUT GONGGONG (THE EFFECT OF THE USE OF ORGANIC ACIDS TO REDUCE THE LEVELS OF METAL LEAD (Pb) ON THE MEAT OF GONGGONG SNAILS) - Amelia, Fitrah; Ramses, Ramses; Ismarti, Ismarti (Tanjungpura University, 2024)
Pollution that often occurs at sea is heavy metal pollution. Heavy metals that often pollute are Lead metals (Pb). Heavy metal pollution that occurs often has an impact on plants and animals that live in the sea. Animals that are often contaminated with heavy metals are snails because of the nature of snails that can accumulate metals due to their persistent nature, filter feeders, slow movements to avoid metal pollution. The purpose of this study is to reduce metal pollution in seafood, one of the ways that can be done by soaking seafood using organic acids such as tamarind and lime, because organic acids contain citric compounds that can bind to metals. This type of research is an experimental research design with Randomized Pretest-posttest control group design. The experimental design used was a Completely Randomized Design (CRD). Metal content analysis was carried out using the Perkin Elmer Type PinAAcle 900T brand AAS. The results were obtained that tamarind can decrease Pb metal levels in the bark snail meat at optimum conditions at a concentration of 10%, immersion time of 60 minutes and a percentage reduction of 47.1%. While the optimum condition of lime occurs at 10% concentration and soaking time is 30 minutes with a 25% percent decrease. So it can be said that tamarind is better in reducing metal content compared to Lime